Customer retention in freemium applications. Issue 4 (December 2018) - Ross, Nicholas
Abstract Over the last decade, many software companies have moved away from selling traditional packaged goods and toward providing "freemium" services. Under this business model, companies give away their basic product and generate revenue by repeatedly selling additional features and content. With this movement, away from one-off transactions and toward longer-term, repeated customer relationships, businesses are increasingly using analytics to understand their customers' behavior, with retention—a measure of the likelihood that a customer will return—being of particular importance. However, despite the value of measuring customer retention, there is no consensus on its definition. Using a unique dataset of freemium mobile games, this study compares and contrasts four commonly used retention measures and finds that a measure that takes into account when a user interacts with an application provides the highest correlation with future monetization. This study also provides empirical evidence of a positive relationship between customer retention and future monetization.